The dream gatherer : a green rider novella and other stories - Britain, Kristen (Britain, Kristen. Green rider., 2018)
"In The Dream Gatherer, Kristen Britain presents a novella and two short stories set in the universe of her best selling Green Rider series in celebration of the twentieth anniversary of the publication of her first novel, Green Rider."--Amazon.